Defending associative duties - Seglow, Jonathan 1968- (Routledge studies in ethics and moral theory, 2013)
"This book explores the associative duties we owe to our children, parents, friends, colleagues, associates and compatriots and defends a novel account which justifies such duties through the realization of values that are produced in these various kinds of social relationships. Seglow engages with several key contemporary debates including parental rights over childrens education, the burdens of eldercare, permissible partiality to friends, and global justice versus compatriot duties"..